Perspectives of the Professional Standard of a Law Enforcement Officer - Irina G. Bavsun (Сибирское юридическое обозрение, 2016)
Qualification requirements for the positions in the Internal Affairs are analyzed in the article. Basing on the conducted analysis the author concludes that they need reviewing and further elaborating in regard to specification of professional knowledge and skills required for a particular position. This work should be carried out within the development of professional standards that in turn should be logically conformed to educational standards.